The Safety and Efficacy of Continuous Tirofiban as a Monoantiplatelet Therapy in the Management of Ruptured Aneurysms Treated Using Stent-Assisted Coiling or Flow Diversion and Requiring Ventricular Drainage. Issue 6 (12th July 2019) - Limaye, Kaustubh; Zanaty, Mario; Hudson, Joseph; Nakagawa, Daichi; Al Kasab, Sami; Alvarez, Carlos; Dandapat, Sudeepta; Kung, David K; Ortega-Gutierrez, Santiago; Jabbour, Pascal; Samaniego, Edgar A; Hasan, David
Abstract: BACKGROUND: Hemorrhagic complications are a major concern for aneurysmal subarachnoid hemorrhage patients treated with stenting or stent-assisted coiling and undergoing additional procedures such as shunting, ventriculostomy placement, and craniotomies/craniectomies. OBJECTIVE: To assess the safety and efficacy of using a continuous infusion of tirofiban as a monoantiplatelet therapy in the management of ruptured aneurysms in the setting of either stent-assisted coiling (SAC) or flow diversion devices (FDD) in patients requiring either an external ventricular drain (EVD) or ventriculoperitoneal shunt (VPS). METHODS: Aneurysmal subarachnoid hemorrhage (aSAH) patients between July 2017 and September 2018 who were treated with SAC or FDD were started on a continuous tirofiban infusion protocol (0.10 μg/kg/min) with no preceding loading dose as a monoantiplatelet therapy. Safety analysis was performed retrospectively to assess the complication rate, hemorrhagic rate, and rate of ischemic events. There were no hemorrhages related to the VPS surgery. RESULTS: Nineteen subjects were included in the series. The patients received a total of 25 procedures that included 19 EVDs and 6 VPSs. Two patients (8.3%) developed small asymptomatic track hemorrhages after EVD placement. One patient developed a large retroperitoneal hemorrhage due to renal artery branch injury during procedure, and another patient developed an idiosyncratic transient thrombocytopenia which resolved after stopping the medication. One patient (4%) developed a transient ischemic attack, which resolved after a bolus of tirofiban. CONCLUSION: Our study suggests that long-term use of intravenous tirofiban monotherapy in aSAH subjects for endovascular SAC or FDD is safe in the perioperative setting. Graphical Abstract: